C. Pareto’s Rule 80/20 Pareto’s Rule on global wealth and material distribution: The role of start-ups to change the dynamics of the rule - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
Pareto Rule of 80/20 has a lot to inform the globe of the inequalities that prevail in human and business systems. This Rule of 80/20 was first postulated by Juran in 1937, however the principles are still applicable in the modern society. It is so unfortunate that the 20% who controls 80% (vital few) of the global wealth, is still sustained. The 80% who controls only 20% (trivial many) of the global income still find themselves constricted to that position. This is a pathetic situation, and governments should do well to help start-ups and the marginalised in societies to extricate themselves from this mess. Poverty or unfair distribution of wealth should not be accepted as the order of life, and individuals should do well to come out of it. It is the hope of this article that when start-ups are given the necessary push by government to be sustainable, there would be a paradigm shift within the 80/20 Rule of Pareto